Battery thermal management based on multiscale encapsulated inorganic phase change material of high stability. (5th July 2021) - Ling, Ziye; Li, Suimin; Cai, Chuyue; Lin, Shao; Fang, Xiaoming; Zhang, Zhengguo
Graphical abstract: Highlights: An effective method to prevent dehydration and improve stability of inorganic PCM. Applies a nonflammable inorganic PCM for battery thermal management. Inorganic PCM has a large thermal conductivity, small subcooling and high stability. Inorganic PCM shows better cooling performance in a battery pack than organic PCM. Abstract: This paper proposes a battery thermal management system with an inorganic phase change material(PCM). A multiscale encapsulation method is presented to solve the inherent problems of the inorganic PCM-sodium acetate trihydrate (SAT)-Urea. This method adopts microscale encapsulation with expanded graphite (EG) to enhances the thermal conductivity of the PCM to 4.96 W/m·K and eliminates the liquid leakage. Further macroscale encapsulation with the organosilicon sealant significantly improves the long-term stability of the salt hydrate, because it completely cuts off the dehydration channel of the salt hydrate, maintaining a stable composition in the PCM. This effective multiscale encapsulation paves the way of applications of the inorganic PCMs in Li-ion battery thermal management. This inorganic PCM is compared with an organic PCM in the fire resistivity and cooling performance for a 20-cell battery pack. The results confirm that the inorganic PCM is safer because it is not flammable and offers a cooler but a more uniform thermal environment for the battery. The competitive inorganic PCM owns advantages in price, safety and cooling performance, showing great prospects in commercial battery thermal management systems.